Analysis of The Supply Chain Performance of Sugar Palm Fruit in Tasikmalaya Regency, West Java - Apriyani, Dwi; Bahar, Rizki Risanto; Mutiarasari, Nurul Risti (Kadiri University - Faculty of Agriculture, 2025)
During Ramadan, demand for palm fruit (kolang kaling) increases by approximately 60%. However, fulfillment of this demand is constrained by the limited availability of palm trees, weak coordination among supply chain actors, and delivery delays. This study aims to describe the overall condition of the palm fruit supply chain and evaluate its performance. A mixed-methods approach was employed, utilizing qualitative analysis through the Food Supply Chain Network (FSCN) framework to map the supply chain, and quantitative analysis using the SCOR model to assess performance. Sampling was conducted through purposive sampling, targeting farmers and processors with consistent production, complemented by snowball sampling to reach actors not easily identified through formal data. The findings indicate that the target market for palm fruit extends beyond local consumption to regional markets. The supply chain structure consists of interdependent collaboration among farmers, artisans, intermediaries, wholesalers, and retailers, and is characterized by three principal flows: product, information, and finance. Constraints are evident in the limited availability of technological and equipment resources. Business processes employ push and pull strategies, depending on demand fluctuations. Performance evaluation reveals weaknesses in several indicators, particularly order fulfillment, compliance with quality standards, asset management, and supply chain cost efficiency. These limitations highlight the urgency of establishing an association of palm fruit supply chain actors to strengthen communication and coordination, thereby supporting the development, sustainability, and competitiveness of palm fruit farming.